Perencanaan dan Analisis Perkuatan Lereng Menggunakan Fondasi Micropiles - Wirman Hidayat; Rangga Adiprima Sudisman; Arlyn Aristo Cikmit (Jurnal Aplikasi Teknik Sipil, 2023)
Slope reinforcement design with micropile is one of the methods commonly used to improve the stability of unstable slopes, the main advantage of using micropile is that it has a high resistance capacity, easy to construct, and can be carried out in a limited work area. In this study, a micropile design was carried out to improve slope stability, then a study was conducted on the effect of pile installation distance (spacing) on the structural behavior of the micropile, namely shear resistance and bending moment, the analysis was carried out using limit-equilibrium method and finite element method. It was found that the micropile design carried out can increase the safety factor of unstable slopes (FS = 1.01) to meet the criteria (FS = 1.51). The results of the study on the effect of pile installation distances show that the shear resistance and bending moment per pile decrease when the installation distance between piles decreases, this is due to the effect of reduction in bearing capacity of the pile group